Wybrane elementy sztuki muzycznej w terapii mowy - Dolińska-Zygmunt, Grażyna; Golema, Amelia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Recently, music art has been more and more often used in the rehabilitation. The following text analyzes two aspects of music art: rhythmics and logorythmics. Descripted methods may be used in therapy with children, teenagers and adults. The author presents Dalcroze's rhythmics and elements of logorhythmics in speech therapy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 214-219